(untitled) - Madura, Jeff (Australia, 2008)
This book presumes an understanding of basic corporate finance. It is suitable for both undergraduate and master's level courses in international financial management. For master's courses, the more challenging question, problems, and cases in each chapter are recommemded, along with special projects.
Keywords: International business enterprises,Corporations; Finance,Finance